Maharah al-Qira'ah Learning Model through Edmodo at Department of Arabic Language Education, Imam Bonjol State Islamic University, Padang - Putri, Neli; Rahmawati, R.; Hanomi, H. (Institut Agama Islam Negeri Curup, 2021)
This study aims to determine the validity of Maharatul Qira'ah learning model design by utilizing Edmodo e-learning application, and to describe the learning model and its impact on student participation. The rapid development of ICT is influencing the Arabic learning model at PBA UIN IB Padang which is still using the classical model, and the participation of students is still lacking. Here, the innovation of the classical learning model toward online-based learning needs to be done, such as by utilizing Edmodo e-learning application. This research used the ADDIE step model. The research subjects consisted of 32 students and 5 lecturers of PBA.Â This study used valid instruments. Based on the data analysis, the validity of the design of the teaching materials presented in the Edmodo e-learning has met the very valid criteria, with a score of 83.59.Â The e-learning model developed was a blended learning with complement functions in the form of synchronous and asynchronous communication. This e-learning had been able to increase student participation by 81,25%.Â This study recommends further researchers to use Edmodo e-learning application in teaching various language skills in a fully integrated online model.